2007
DOI: 10.1128/jcm.01234-07
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Region of Difference 1 among Clinical Isolates of Mycobacterium tuberculosis from India

Abstract: ᰔRegion of difference 1 (RD1) was first described by Mahairas et al. (4) as a region that is present in all virulent laboratory and clinical strains of Mycobacterium bovis and Mycobacterium tuberculosis. This region comprises nine genes (Rv3871 to Rv3879c) and spans a 9.5-kb region. In M. bovis BCG, RD1 deletion completely removes seven genes (Rv3872 to Rv3878) and truncates two others (Rv3871 and Rv3879c) (3). Recently Rao et al. (5) reported the total absence of RD1 in clinical isolates from India. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In fact, few isolates we obtained from Hyderabad were found positive for RD1 region in all the isolates (data not shown). This is in concurrence with other reports [ 11 , 4 ].…”
Section: Discussionsupporting
confidence: 94%
“…In fact, few isolates we obtained from Hyderabad were found positive for RD1 region in all the isolates (data not shown). This is in concurrence with other reports [ 11 , 4 ].…”
Section: Discussionsupporting
confidence: 94%
“…The best known example of a well-studied pathogen and granuloma is Mtb. Experimental studies in Mtb suggested that RD1 locus proteins 28 , ESAT-6 secretion system proteins 29 and proteins of intra-macrophage secretome 30 were mainly involved in Mtb granuloma. Several studies indicated the importance of RD1 locus and ESAT-6 secretion system in Mtb granuloma [71][72][73] .…”
Section: Discussionmentioning
confidence: 99%
“…A composite interaction network of RD1 locus proteins 28 , ESAT-6 secretion system proteins 29 and intra-macrophagic secretome of Mtb 30 was created using STRING database, at confidence score 0.150. The Mtb orthologs of the proposed seven Yps granuloma proteins were mapped on this interaction network.…”
Section: Mapping Of Yps Predicted Proteins On Composite Ppi Interactimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, considering that suspected tuberculous lymphadenitis patients without an identifiable tuberculous contact were subject to further investigations for differential diagnosis of M. bovis BCG, we performed the tar- tuberculosis complex members, enabling us to differentiate different strains belonging to the M. tuberculosis complex and making surveillance of speciesspecific disease suitable 13,14) . This diagnostic method could help to confirm BCG lymphadenitis.…”
Section: Discussionmentioning
confidence: 99%